2015
DOI: 10.1007/s11120-015-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of the emission spectra of various photosystem II core complexes

Abstract: We evaluate low-temperature (low-T) emission spectra of photosystem II core complexes (PSII-cc) previously reported in the literature, which are compared with emission spectra of PSII-cc obtained in this work from spinach and for dissolved PSII crystals from Thermosynechococcus (T.) elongatus. This new spectral dataset is used to interpret data published on membrane PSII (PSII-m) fragments from spinach and Chlamydomonas reinhardtii, as well as PSII-cc from T. vulcanus and intentionally damaged PSII-cc from spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…These data clearly indicate that absorption of the CP47 complex has experienced nonphotochemical HB at 5 K and that the 695 nm emission of CP47 is consistent with that observed for intact PSII-cc samples (for more details, see Ref. 39 ). Only data in Figure 2B are consistent with Figure 3 .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These data clearly indicate that absorption of the CP47 complex has experienced nonphotochemical HB at 5 K and that the 695 nm emission of CP47 is consistent with that observed for intact PSII-cc samples (for more details, see Ref. 39 ). Only data in Figure 2B are consistent with Figure 3 .…”
Section: Resultssupporting
confidence: 82%
“…We emphasize again that only the redshifted emission near 695 nm (see Fig. 2B ) is clearly observed in PSII membrane fragments 41 , 45 , 46 and PSII-cc from Thermosynechococcus elongatus , 39 which are considered to be intact preparations. Figure 3 shows 5 K PSII-cc emission spectra before and after HB (curves a and b, respectively), while the inset shows 77 K spectra of intact PSII-cc and CP47 (red curve).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Chen et al (2015) made an extensive comparison between published results and new fluorescence emission spectra recorded on isolated PSII cores of spinach and from re-dissolved PSII core crystals of the cyanobacterium Thermosynechococcus elongatus . The authors showed that isolation procedures that preserve the intactness of the PSII core result in nearly overlapping 77 K emission spectra of cyanobacteria, the green alga Chlamydomonas reinhardtii and spinach.…”
Section: Question 17: Can the 77 K Fluorescence Emission Bands Be Assmentioning
confidence: 99%
“…To understand the significance of PsbH in the context of light‐harvesting, we have to consider low‐energy states that have been discovered in many photosynthetic systems as reviewed by Reimers et al These states become manifest in optical absorptions energetically well below that of the RC, that is, in the case of PSII at wavelengths larger than about 680 nm (see also the discussion of the RC absorption spectrum below). A distinction has to be made between extremely red‐shifted states of yet unknown origin and more moderately red‐shifted states giving rise to absorption at 694 nm as well as corresponding emission signals . We are only concerned with the latter type of states here.…”
Section: Pigments and Lipids Of The Core Complexmentioning
confidence: 99%